Implementasi Transisi Finite State Automata dengan Aplikasi Mesin Abstrak DFA dan NFA berbasis Android - Syahbani Farhan; Iskandar Fitri; Fauziah (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2021)
Language and automata are important sciences that make them the main components in making software. If one of them does not have these components, there will be an imbalance or even fail to make a software. Because language is a tool used daily in communicating both to humans and computers. While automata is a process that can operate alone, by having a theory about abstract machines and is closely related to language. Automata has a relationship in the form of grammar, where the grammar is an abstract form that can reject if the input string we entered is wrong and accept if the input string we entered is correct to generate an output that matches the input. The purpose of this study is to test the theories of Language and Automata to be verified by making DFA and NFA abstract machine applications using Android Studio. The results shown by the Abstract Machine application that have been made are able to read and process numbers with an integer range of 2,147,483,647 and also the level of accuracy of reading data in each state process is 90.00% or 36 data that were successfully tested without experiencing errors from 40 data that have been tested on application.